PENGEMBANGAN MEDIA INTERAKTIF BERBASIS GOOGLE SITES PADA MATERI TANDA BACA DAN HURUF KAPITAL SISWA KELAS III SD - Idawati Idawati; Hendra Nelva Saputra; Zila Razilu (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
This study was motivated by the limited use of digital interactive learning media in Indonesian language learning at the elementary school level, which has resulted in students experiencing difficulties in understanding the proper use of punctuation marks and capital letters in accordance with Indonesian language conventions. This study aimed to develop an interactive learning media based on Google Sites for the topic of punctuation marks and capital letters for third-grade elementary school students and to determine the validity and practicality of the developed media. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The product developed was an interactive learning media based on Google Sites that integrates learning materials, images, instructional videos, and Google Forms-based evaluations into a single online-accessible platform. The research subjects consisted of 29 third-grade students of SDN 98 Kendari as the target class, three material experts, and three media experts, while user testing was conducted with 10 students. Data were collected through observation, interviews, documentation, and questionnaires using a Likert scale. The results showed that the developed media obtained a material expert validation score of 94.2% and a media expert validation score of 95%, both categorized as highly valid. In addition, the student response results achieved an average percentage of 82.5%, categorized as highly practical. These findings indicate that the developed media meets the criteria of validity and practicality and can therefore be used as an alternative learning medium for Indonesian language instruction on punctuation marks and capital letters for elementary school students. ABSTRAK Penelitian ini dilatarbelakangi oleh terbatasnya penggunaan media pembelajaran interaktif berbasis digital dalam pembelajaran Bahasa Indonesia di sekolah dasar, sehingga siswa mengalami kesulitan dalam memahami penggunaan tanda baca dan huruf kapital sesuai kaidah bahasa Indonesia. Penelitian ini bertujuan untuk mengembangkan media interaktif berbasis Google Sites pada materi tanda baca dan huruf kapital untuk siswa kelas III sekolah dasar serta mengetahui tingkat kelayakan dan kepraktisan media yang dikembangkan. Penelitian ini menggunakan metode Research and Development (R&D) dengan model ADDIE yang meliputi tahap analysis, design, development, implementation, dan evaluation. Produk yang dihasilkan berupa media pembelajaran interaktif berbasis Google Sites yang mengintegrasikan materi pembelajaran, gambar, video pembelajaran, dan evaluasi berbasis Google Forms dalam satu media yang dapat diakses secara daring. Subjek penelitian terdiri atas 29 siswa kelas III SDN 98 Kendari sebagai kelas sasaran, 3 ahli materi, dan 3 ahli media, sedangkan uji coba pengguna dilakukan kepada 10 siswa. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dokumentasi, dan angket menggunakan skala Likert. Hasil penelitian menunjukkan bahwa media yang dikembangkan memperoleh persentase validasi ahli materi sebesar 94,2% dan validasi ahli media sebesar 95% dengan kategori sangat valid, sedangkan hasil respon siswa memperoleh rata-rata persentase sebesar 82,5% dengan kategori sangat praktis. Temuan tersebut menunjukkan bahwa media yang dikembangkan telah memenuhi kriteria kelayakan dan kepraktisan sehingga dapat digunakan sebagai alternatif media pembelajaran Bahasa Indonesia pada materi tanda baca dan huruf kapital untuk siswa sekolah dasar.